Ultrasound-based lipid content quantification using double Nakagami distribution model in rat liver steatosis. (22nd May 2020) - Tamura, Kazuki; Mamou, Jonathan; Yoshida, Kenji; Hachiya, Hiroyuki; Yamaguchi, Tadashi
Abstract: Quantitative ultrasound (QUS) methods have been widely used for soft tissue characterization. Spatial resolution (i.e. ultrasound frequency) is an important factor for QUS methods. In a previous study, a double Nakagami (DN) distribution model to echo signals from fatty livers using a 15 MHz transducer was used to permit fine-resolution QUS. This study used a filtering approach to quantify steatosis progression using three QUS parameters obtained by fitting a DN distribution model to experimental envelope data. The filter was designed using QUS parameters obtained from three healthy liver. A strong correlation ( r = 0.96, p < 0.001) was found between histologically quantified steatosis percentage and the percentage of the liver having non-healthy liver features. This approach was able to successfully diagnose fatty livers (>20% steatosis percentage) in a dataset of 12 livers ranging from 0% to 90% steatosis.